New Horizons of Parallel and Distributed Computing - Guo, Minyi; Yang, Laurence Tianruo (Springer US : Imprint: Springer, 2005)
Parallel and distributed computing is one of the foremost technologies for shaping future research and development activities in academia and industry. Hyperthreading in Intel processors, hypertransport links in next generation AMD processors, multicore silicon in today's high-end microprocessors, emerging cluster and grid computing, has moved parallel/distributed computing into the mainstream of computing. New Horizons of Parallel and Distributed Computing is a collection of self-contained chapters written by pioneers and researchers to provide solutions for newly emerging problems in this field. This volume will not only provide novel ideas, work in progress and state-of-the-art techniques in the field, but also stimulate future research activities in the area of parallel and distributed computing with applications. New Horizons of Parallel and Distributed Computing is intended for researchers and graduate students in computer science and electrical engineering, as well as researchers and developers in industry. This book can be used as a textbook and a reference for use by students, researchers, and developers.